Zechariah 8 as revision and digest of Zechariah 1-7 - ʿAsis, Eliyahu (The journal of Hebrew scriptures, 2010)
It is generally accepted that Zech 1–8 consists of two distinct sections: Zech 1–6 and Zech 7–8. This article argues that the main divide is between chapters 1–7 and ch. 8. Zech 8 is a collection of oracles that offers a revision and digest of sections of the previous chapters in Zech 1–7. These oracles re-quote key phrases of units in Zech 1–7, re-word similar ideas, or use different wordings for similar ideas. Texts in Zech 8, at times, modify those they parallel or complete them. In addition, this article shows that a characteristic feature of many of the literary units in chapter 8, in comparison with chapters 1–7, is that they emphasize greater hope and comfort.